1983
DOI: 10.1007/bf01120703
|View full text |Cite
|
Sign up to set email alerts
|

A multiplicity of erythrocyte glycolipids of the neolacto series revealed by immuno-thin-layer chromatography with monoclonal anti-I and anti-i antibodies

Abstract: The thin-layer-chromatography immunostaining procedure was applied to human erythrocyte glycolipids using monoclonal anti-i and anti-I antibodies which are directed against epitopes on linear and branched carbohydrate chains of the neolacto (poly-N-acetyllactosamine) series. An examination of native and mild-acid-treated glycolipids from normal adult (I(adult) antigen type), neonatal (i(cord)), and I-antigen-deficient adult (i(adult)) erythrocytes enabled certain structural inferences to be made as follows: (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…We have observed that under the conditions used by Woodward et al (1985) the linear poly-N-acetyl-lactosamine determinant recognised by an anti-i antibody (Tho) and the branched poly-N-acetyllactosamine determinant recognised by anti-I (Step) that are expressed on meconium glycoproteins and sheep gastric mucins, respectively, are not destroyed, whereas SSEA-1, i (Den), on meconium, and I (Ma), on sheep gastric mucins, are destroyed (P. W. Tang & T. Feizi, unpublished work). Both the anti-i Tho and anti-I Step (Gardas, 1982;Uemura et al, 1983) can react with internal domains of poly-N-acetyllactosamine chains and do not require terminal galactose residues to be present. In contrast, anti-SSEA-1 has a strict requirement for a l-3-linked terminal fucose Hounsell et al, 1981) and anti-I Ma and anti-i Den require terminal galactose residues (Feizi et al, 1971;Tang et al, 1986).…”
Section: Glycoprotein Oligosaccharides As Major Antigens Of Whole Cellsmentioning
confidence: 99%
“…We have observed that under the conditions used by Woodward et al (1985) the linear poly-N-acetyl-lactosamine determinant recognised by an anti-i antibody (Tho) and the branched poly-N-acetyllactosamine determinant recognised by anti-I (Step) that are expressed on meconium glycoproteins and sheep gastric mucins, respectively, are not destroyed, whereas SSEA-1, i (Den), on meconium, and I (Ma), on sheep gastric mucins, are destroyed (P. W. Tang & T. Feizi, unpublished work). Both the anti-i Tho and anti-I Step (Gardas, 1982;Uemura et al, 1983) can react with internal domains of poly-N-acetyllactosamine chains and do not require terminal galactose residues to be present. In contrast, anti-SSEA-1 has a strict requirement for a l-3-linked terminal fucose Hounsell et al, 1981) and anti-I Ma and anti-i Den require terminal galactose residues (Feizi et al, 1971;Tang et al, 1986).…”
Section: Glycoprotein Oligosaccharides As Major Antigens Of Whole Cellsmentioning
confidence: 99%
“…Immunostaining was performed using as antigen about 2^g of gangliosides obtained from AIDS lymphocytes. Gangliosides were separated by TLC, using HPTLC aluminium backed silica gel 60 (20x20) plates (Merck) [21]. Plates were soaked in a 0.2% solution of polyisobuthylmethacrylate in hexane for 90s, air dried and incubated in the blocking solution 3% bovine serum albumin (BSA) in 20 mmol Tris 0.5M NaCl, pH 7.5 (BSA-TBS) for lh at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…lA and 1 B) which are known to be predominantly of the neolacto-series (Chien et al, 1978;Hakomori, 1981). The majority of immunoreactive glycolipid bands were clustered as two groups, the first migrating in the region of the GD1Ia standard and sialosylneolactohexaosylceramides and the second in the region of GDl b and GT1 b and slow migrating components corresponding to more complex gangliosides of the neolacto series (Feizi et al, 1978;Uemura et al, 1983). Some reactivity in the region-of GN13 was also present ( Fig.…”
Section: Glycolipids Expressing the Pr2 Determinantmentioning
confidence: 99%
“…Human brain gangliosides were prepared according to Ledeen -t -t cytes were used after storage at 4°C for 5 days and the iadult cells at -20°C in glycerol for 9 months according to Mollison (1979). From erythrocyte membranes (Dodge et al, 1963), glycolipids were extracted (Uemura et al, 1983) and evaporated to dryness. The dried residue was treated with 0.1 M-NaOH for 1 h at room temperature and dialysed against water, evaporated and finally dissolved in chloroform/methanol (1:…”
mentioning
confidence: 99%
See 1 more Smart Citation